Comparative clinical implications of admission electrocardiographic findings for patients with non-ST-segment elevation myocardial infarction. Issue 37 (September 2016) - Jin, Eun-Sun; Park, Chang-Bum; Kim, Dong-Hee; Hwang, Hui-Jeong; Cho, Jin-Man; Sohn, Il Suk; Kim, Chong-Jin
Abstract : Abstract: Early risk stratification is crucial for appropriate management using invasive strategies in non-ST elevation myocardial infarction (NSTEMI), and electrocardiography (ECG) has been widely used for risk stratification. However, ECG findings in NSTEMI vary, and there is a need to define the clinical characteristics and outcomes according to ECG. We analyzed the admission ECGs of 345 NSTEMI patients who underwent coronary angiography from 2006 to 2013. Demographics, procedural characteristics, and clinical outcomes were analyzed. The ST-segment depression, T-wave inversion, and no ECG change groups included 114, 90, and 141 patients, respectively. The ST-segment depression group trended toward older, nonsmoking, and female, with a lower body mass index (BMI) and a higher incidence of comorbidities, than the no ECG change group. The ST-segment depression group also had a higher Killip class, a lower left ventricular ejection fraction, a higher regional wall motion score index (RWMSI), and 3-vessel coronary artery disease angiographically, than the no ECG change group. Patients with T-wave inversion trended toward older, female, lower BMI, less smoking, lower creatine kinase MB, and more left anterior descending (LAD) artery involvement, than the no ECG change group. In clinical outcomes, the ST-segment depression group had a higher mortality rate at 30 days and 12 months after the index procedure than the no ECG change group, whereas the T-wave inversion group showed similar clinical outcomes. Patients with ST-segment depression have a greater burden of comorbidities with risk factors and worse clinical outcomes, whereas patients with T-wave inversion have an intermediate number of risk factors but similar outcomes, compared with the no ECG change group. Further study is necessary to evaluate the prognostic impact of the baseline ECG on admission.